The Taurine Transporter Eaat2 Functions in Ensheathing Glia to Modulate Sleep and Metabolic Rate. - Stahl, B.A.; Peco, E.; Davla, S.; Murakami, K.; Caicedo Moreno, N.A.; van Meyel, D.J.; Keene, A.C. (Current Biology, 2018)
Sleep is critical for many aspects of brain function and is accompanied by brain-wide changes in the physiology of neurons and synapses [1, 2]. Growing evidence suggests that glial cells contribute to diverse aspects of sleep regulation, including neuronal and metabolic homeostasis [3-5], although the molecular basis for this remains poorly understood. The fruit fly, Drosophila melanogaster, displays all the behavioral and physiological characteristics of sleep [1, 2], and genetic screening in flies has identified both conserved and novel regulators of sleep and wakefulness [2, 6, 7]. With this approach, we identified Excitatory amino acid transporter 2 (Eaat2) and found that its loss from glia, but not neurons, increases sleep. We show that Eaat2 is expressed in ensheathing glia, where Eaat2 functions during adulthood to regulate sleep. Increased sleep in Eaat2-deficient flies is accompanied by reduction of metabolic rate during sleep bouts, an indicator of deeper sleep intensity. Eaat2 is a member of the conserved EAAT family of membrane transport proteins [8], raising the possibility that it affects sleep by controlling the movement of ions and neuroactive chemical messengers to and from ensheathing glia. In vitro, Eaat2 is a transporter of taurine [9], which promotes sleep when fed to flies [10]. We find that the acute effect of taurine on sleep is abolished in Eaat2 mutant flies. Together, these findings reveal a wake-promoting role for Eaat2 in ensheathing glia through a taurine-dependent mechanism.